2013
DOI: 10.4283/jmag.2013.18.3.289
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rotating Magnetic Field on Growth Rate, Cell Metabolic Activity and Biofilm Formation by Staphylococcus Aureus and Escherichia Coli

Abstract: This work presents results of the study which concerns the influence of the rotating magnetic field (RMF) on the growth rate, cell metabolic activity and ability to form biofilms by E. coli and S. aureus. Liquid cultures of the bacteria were exposed to the RMF (RMF frequency f = 1-50 Hz, RMF magnetic induction B = 22-34 mT, time of exposure t = 60 min, temperature of incubation 37 °C). The present study indicate the exposition to the RMF, as compared to the unexposed controls causing an increase in the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 43 publications
5
30
0
1
Order By: Relevance
“…The present work is a continuation of our previous study [20] in which we investigated whether the RMF, depending on magnetic induction, frequency and time of exposure, can influence on the growth dynamics, cell metabolic activity and other biochemical processes in various microorganism, including S. aureus. In the current study, we investigated the effect of the RMF exposure on pathogenic potential of S. aureus strains expressed by the changes in activity of genes encoding staphylococcal enterotoxins.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The present work is a continuation of our previous study [20] in which we investigated whether the RMF, depending on magnetic induction, frequency and time of exposure, can influence on the growth dynamics, cell metabolic activity and other biochemical processes in various microorganism, including S. aureus. In the current study, we investigated the effect of the RMF exposure on pathogenic potential of S. aureus strains expressed by the changes in activity of genes encoding staphylococcal enterotoxins.…”
Section: Resultsmentioning
confidence: 91%
“…The exposition of bacteria to the RMF was carried out using self-designed set-up, described in our previous work [20] and adopted for purposes of this research. This set-up is schematically presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous reports showing that MFs may have infl uence on microorganisms and thus change their biotechnological potential [16][17][18] . The research concerning the use of MFs in the biotechnological engineering conducted to date have concerned mostly static magnetic fi elds (SMFs), whereas the biotechnologically promising idea to use rotating magnetic fi elds (RMFs) is developed just relatively recently [19][20][21] . In previous studies we showed that the RMF can be used to increase (over 20% compared to the bacteria non-exposed to RMF) the growth and cell metabolic activity of such microorganisms as Staphylococcus aureus, Escherichia coli, Serratia marcescens, Streptococcus mutans, Cronobacter sakazakii, Klebsiella oxytoca and Staphylococcus xylosus) [20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The research concerning the use of MFs in the biotechnological engineering conducted to date have concerned mostly static magnetic fi elds (SMFs), whereas the biotechnologically promising idea to use rotating magnetic fi elds (RMFs) is developed just relatively recently [19][20][21] . In previous studies we showed that the RMF can be used to increase (over 20% compared to the bacteria non-exposed to RMF) the growth and cell metabolic activity of such microorganisms as Staphylococcus aureus, Escherichia coli, Serratia marcescens, Streptococcus mutans, Cronobacter sakazakii, Klebsiella oxytoca and Staphylococcus xylosus) [20][21] . Similarly, the current study also showed that, depending on its mode, RMF exposure increased the growth of G. xylinus by as much as 43% as compared to the control unexposed cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Matwijczuk et al (2011), juga menyatakan bahwa pemaparan medan magnet baik pada biji bunga matahari langsung maupun pada air untuk menyiram kecambah bunga matahari dapat meningkatkan kecepatan perkecambahan. Fijalkowski, et al (2013), menyatakan bahwa pemaparan medan magnet pada bakteri Escherichia Coli dan Staphylococcus Aureus dengan frekuensi 1 -50 Hz selama 60 menit pada suhu inkubasi 37 °C dapat meningkatkan pertumbuhan, aktivitas metabolisme dan kemampuan pembentukan bio-film. Hasil yang berbeda ditunjukkan dari hasil penelitian Fojt, et al (2009) yang menyatakan bahwa pemaparan medan magnet yang semakin lama, mengakibatkan penurunan pertumbuhan bakteri E. coli dan P. denitrificans.…”
Section: Uji Pengaruh Medan Magnetunclassified